Therapeutic potential of interleukin-21 in cancer - Isvoranu, Gheorghita; Chiritoiu-Butnaru, Marioara (Frontiers in Immunology, 2024)
Interleukin-21 (IL-21) is an immunostimulatory cytokine which belongs to the common gammachain family of cytokines. It plays an import role in the development, differentiation, proliferation, and activation of immune cells, in particular T and natural killer (NK) cells. Since its discovery in 2000, IL-21 has been shown to regulate both adaptive and immune responses associates with key role in antiviral and antitumor responses. Recent advances indicate IL-21 as a promising target for cancer treatment and encouraging results were obtained in preclinical studies which investigated the potency of IL-21 alone or in combination with other therapies, including monoclonal antibodies, checkpoint inhibitory molecules, oncolytic virotherapy, and adoptive cell transfer. Furthermore, IL-21 showed antitumor effects in the treatment of patients with advanced cancer, with minimal side effects in several clinical trials. In the present review, we will outline the recent progress in IL-21 research, highlighting the potential of IL-21 based therapy as single agent or in combination with other drugs to enhance cancer treatment efficiency.